ANALISIS WANITA KARIR DALAM MENUNJANG KEBUTUHAN EKONOMI KELUARGA DI KELURAHAN SUNGAI BANGKONG KECAMATAN PONTIANAK KOTA - Yola Febryani; Rustiyarso Rustiyarso; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research was aimed to find out the career women’s activities to support the economic needs of families in Sungai Bangkong Urban Village, Pontianak Kota Sub-district. The general problem of this research was “How did career women support economic needs of families in Sungai Bangkong Urban Village, Pontianak Kota Sub-district?” The research method used was descriptive in qualitative form. The data collection techniques employed were observation, interview and documentation. The data collection tools used were observation guidelines, interview guidelines and documentation. The data analysis of this research was presented in descriptive qualitative form with 3 informants that is, 3 career women in Sungai Bangkong Urban Village of Pontianak Kota Sub-district. The results showed that the women worked with the intention to support the economy of families in terms of factors affecting types of jobs, work intensity, and income earned by career women in Sungai Bangkong Urban Village, Pontianak Kota Sub-district. Keywords: Analysis, Career Women, Family Economy.